APPLICATION OF ULTRASONIC TECHNOLOGIES IN ORTHOPEDIC DENTISTRY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Ultrasonic technologies, introduced in dentistry since the mid-20th century, have revolutionized various dental procedures, including periodontitis treatment and dental plaque removal. Ultrasonic devices used in dental practices typically consist of piezoceramic, magnetostrictive, or aerodynamic transducers that operate within a frequency range of 20-45 kHz. In orthopedic dentistry, ultrasonic tools have proven highly effective for minimally invasive preparation of dental tissues, ensuring precision and reducing trauma to both hard and soft tissues. This review explores the application of ultrasonic technologies in orthopedic dentistry, including the benefits, mechanisms, and clinical uses in procedures such as the removal of dental restorations, condensation of cements, and physiotherapeutic treatments. It also examines the advantages of specific tools used for precise preparation in aesthetically significant areas, the management of implants, and de-cementing crowns and bridges. The paper highlights advancements in ultrasonic instrumentation that improve the functionality, longevity, and aesthetic outcomes of indirect restorations.